REMOVAL OF MACROLYDES FROM WATER. ANALYTICAL REMOVAL TECHNIQUES. AN OVERVIEW. - Zuñiga D, Martina; Rivas, Bernabe L (Journal of the Chilean Chemical Society, 2023)
Water is an essential substance to ensure the survival of human beings has been contaminated over the years, which has been reflected in the increase of contamination by substances from industry and domestic waste, deteriorating its quality and turning it into a risk for those who consume it or live in it. However, in recent years the interest of researchers to remedy this problem has led to the study of different techniques applied to remove these contaminants since the traditional methods used in water treatment plants do not satisfactorily fulfill this purpose. Among the contaminants of greatest interest and to which this review is directed are the emerging contaminants, substances at trace level of a large number of chemical compounds of different origin and nature, which accumulate in aquatic environments causing cardiac affections, psychiatric reactions, liver disorders, genetic mutation, ecotoxicological risks as well as bacterial resistance, such as macrolides. These compounds belong to the group of antibiotics used to treat mainly respiratory affections, but whose consumption has increased in the last couple of years due to their possible action for the prevention of contagion or reduction of symptoms in patients with the COVID-19 virus. Therefore, the objective of this review is to compile the techniques used for their removal, such as sonochemical treatment and continuous ozonation, from which removal percentages higher than 70% have been obtained for macrolides such as azithromycin, clarithromycin, and erythromycin, representative drugs of this type of antibiotics, this in order to conduct research and experimental work for the removal with techniques such as polymer-assisted liquid phase retention, ultranofiltration membranes, which have had high percentages of efficiency for different types of antibiotics and thus establish different ways of removal for these contaminants of interest.